4-Bromo-2-{[4-(3-mesityl-3-methylcyclobutyl)thiazol-2-yl]hydrazonomethyl}phenol, with N-H•••N,C-H•••? and ?-? interactions - Soylu, MS; Çaliskan, N; Çukurovali, A; Yilmaz, I; Büyükgüngör, O (Int Union Crystallography, 2005)
The title compound, C24H26BrN3OS, crystallizes in the triclinic space group P (1) over bar, with two independent molecules in the asymmetric unit. The molecules adopt an E geometry about the azomethine C=N double bond. The structure is stabilized as dimers by N - H center dot center dot center dot N hydrogen bonding. C - H center dot center dot center dot pi and pi-pi interactions are also effective in the crystal packing.